If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + y + z) + (2w + 3y + 7) = 0 Remove parenthesis around (x + y + z) x + y + z + (2w + 3y + 7) = 0 Reorder the terms: x + y + z + (7 + 2w + 3y) = 0 Remove parenthesis around (7 + 2w + 3y) x + y + z + 7 + 2w + 3y = 0 Reorder the terms: 7 + 2w + x + y + 3y + z = 0 Combine like terms: y + 3y = 4y 7 + 2w + x + 4y + z = 0 Solving 7 + 2w + x + 4y + z = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + 2w + x + 4y + -7 + z = 0 + -7 Reorder the terms: 7 + -7 + 2w + x + 4y + z = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 2w + x + 4y + z = 0 + -7 2w + x + 4y + z = 0 + -7 Combine like terms: 0 + -7 = -7 2w + x + 4y + z = -7 Add '-1x' to each side of the equation. 2w + x + 4y + -1x + z = -7 + -1x Reorder the terms: 2w + x + -1x + 4y + z = -7 + -1x Combine like terms: x + -1x = 0 2w + 0 + 4y + z = -7 + -1x 2w + 4y + z = -7 + -1x Add '-4y' to each side of the equation. 2w + 4y + -4y + z = -7 + -1x + -4y Combine like terms: 4y + -4y = 0 2w + 0 + z = -7 + -1x + -4y 2w + z = -7 + -1x + -4y Add '-1z' to each side of the equation. 2w + z + -1z = -7 + -1x + -4y + -1z Combine like terms: z + -1z = 0 2w + 0 = -7 + -1x + -4y + -1z 2w = -7 + -1x + -4y + -1z Divide each side by '2'. w = -3.5 + -0.5x + -2y + -0.5z Simplifying w = -3.5 + -0.5x + -2y + -0.5z
| 20-3y=5.29 | | s^2+2s-19=5 | | 5x-10-5= | | (-x^6+7x^2+11)-(12x^6+4x^5-2x+1)= | | 4x+-3=3x+1 | | -14-2x=5x+10 | | 21.27=4g+3.95 | | a^2+44=b^3 | | 1.26g-6=0.93 | | x^2y-9+3x=x^2y+5 | | 3x+4-5x=5x-10-5x | | 9x-8=126 | | 3x+17x-4=5(4x+3) | | 98+7=s | | 2.875+2T=3.125 | | y=mx+12 | | -7w+15=1 | | Y-7=-6y | | 1x+2=-3x+9 | | 2-7m=-75 | | 3x-c+8+5x-2=10 | | 2-7m=-73 | | 4x^3-20x^2+4x+300=0 | | 6(1x-6)+6=8x-8 | | -16+2x=-6x+32 | | -15x+24y=500 | | -12-9x=53 | | b(3)=21 | | (6x^4-x^3-3x^2+20)+(10x^3-4x^2+9)= | | 2x-42=x | | 6sq^2(3)+4=x | | 4x^2+9y^2=13 |